Bidirectional information sharing between Nagoya Memorial Hospital and health insurance pharmacies using a communication sheet for pharmaceutical cooperation - Megumi Kabeya; Satoshi Hibi; Shu Yuasa; Satoshi Kayukawa; Kenji Ina (BMC, 2020)
Abstract Background We collaborated with the regional pharmaceutical associations near Nagoya Memorial Hospital and created a communication sheet for pharmaceutical cooperation between the hospital and health insurance pharmacies. Methods The communication sheet for pharmaceutical cooperation was issued in October 2014. We conducted a questionnaire survey of both cancer patients and community pharmacists 1 year after the implementation of the use of this sheet. Based on the results of the survey, we modified our communication sheet and added a unified reply form in October 2016. We examined the number of replies from community pharmacists from October 2014 to April 2019. We then analyzed how community pharmacists instructed and communicated with cancer patients using the results of both the questionnaire survey and the reply form, which were compared before and after introducing the modified version of the communication sheet. Results During the 5 years of observation, 743 communication sheets were sent from Nagoya Memorial Hospital to community pharmacists. As a result of pharmaceutical cooperation in using the communication sheet, 96.4% of prescribed medication were immediately prepared in health insurance pharmacies on that day. The communication sheet also enhanced the conversations between cancer patients and pharmacists. The introduction of the unified reply form increased the response rate of community pharmacists from 1.7 to 69.5% (p < 0.001). The communication between community pharmacists and cancer patients was significantly hindered by prescriptions without an oral cancer drug and patient age < 65 years old (p < 0.05). However, this hindrance was reduced by the use of the modified form. Conclusions The communication sheet for pharmaceutical cooperation is useful for bidirectional information sharing between hospitals and health insurance pharmacies, which may enable pharmacists to provide cancer patients with medication instructions in coordination with hospitals and increase the quality of outpatient pharmacy services.